2021
DOI: 10.1111/1750-3841.15819
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and epitope prediction of phosphopyruvate hydratase from Penaeus monodon (black tiger shrimp)

Abstract: Shellfish allergies constitute an important cause of food-induced anaphylactic reactions, which pose challenges to food safety and human health worldwide. In the present study, the specific IgE (sIgE) binding characteristics of different shrimp proteins of black tiger shrimp (Penaeus monodon) to the sera of eight shrimp-allergic patients from China were studied by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) and nanoliquid chromatography time-of-flight mass spectrometry. According to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Recent studies indicate MHC allergenicity in patients with fish allergy [43] and increasing evidence in shellfish allergy. MHC is a potential allergen in P. monodon [44,45] and is cross-reactive with HDM MHC [44]. Studies on banana shrimp (Fenneropenaeus merguiensis) have also found evidence of MHC allergenicity in shrimp-sensitive patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate MHC allergenicity in patients with fish allergy [43] and increasing evidence in shellfish allergy. MHC is a potential allergen in P. monodon [44,45] and is cross-reactive with HDM MHC [44]. Studies on banana shrimp (Fenneropenaeus merguiensis) have also found evidence of MHC allergenicity in shrimp-sensitive patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the report of Yang et al, phosphopyruvate hydratase is an enzyme that participates in glycolysis. 35 Aspartate aminotransferase (AAT) is a member of the cluster that is highlighted in the Figure 3. An investigation indicates that AAT participates in glycolysis and plays a role in electron transfer from NADH.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that eleven (68%) and seven (43%) patients demonstrated IgE-binding activity to titin (Ttn) (identified by mass spectrometry) in raw and heated P. monodon extracts, respectively [29]. Phosphopyruvate hydratase/enolase in P. monodon was identified as a novel, putative shrimp allergen but with a limited number of patients and pediatric patients involved only [73]. Khanaruksombat et al [74] also identified enolase as a potential important allergen in the muscle of P. merguiensis, accompanied with the potential allergen myosin heavy chain (MHC).…”
Section: Other Potential Shrimp Allergensmentioning
confidence: 99%